2020
DOI: 10.3389/fbioe.2020.00229
|View full text |Cite
|
Sign up to set email alerts
|

Decellularized Human Dermal Matrix as a Biological Scaffold for Cardiac Repair and Regeneration

Abstract: The complex and highly organized environment in which cells reside consists primarily of the extracellular matrix (ECM) that delivers biological signals and physical stimuli to resident cells. In the native myocardium, the ECM contributes to both heart compliance and cardiomyocyte maturation and function. Thus, myocardium regeneration cannot be accomplished if cardiac ECM is not restored. We hypothesize that decellularized human skin might make an easily accessible and viable alternate biological scaffold for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 95 publications
2
26
0
Order By: Relevance
“…The fibrinogen hydrogels typically used for bioprinting applications are commonly supplemented with gelatin and hyaluronic acid [22]. DsECM contains multiple ECM components, including collagen I and collagen III fragments, glycoproteins, and glycosaminoglycans [23]. The combination of fibrinogen hydrogel and dsECM in our study supports the structural integrity of the printed construct and provides normal skin ECM components.…”
Section: Resultssupporting
confidence: 65%
“…The fibrinogen hydrogels typically used for bioprinting applications are commonly supplemented with gelatin and hyaluronic acid [22]. DsECM contains multiple ECM components, including collagen I and collagen III fragments, glycoproteins, and glycosaminoglycans [23]. The combination of fibrinogen hydrogel and dsECM in our study supports the structural integrity of the printed construct and provides normal skin ECM components.…”
Section: Resultssupporting
confidence: 65%
“…Allergic and anti-inflammatory side reactions have been reported with some silk derivatives, so care should be taken when incorporating them into an engineered tissue. Amongst natural hydrogels, decellularised ECM (dECM) has attracted significant interest since the breakthrough discovery of the process, as applied to the building of tissues (Ott et al, 2008;Belviso et al, 2020). In principle, dECM retains all components of the ECM of origin, thus creating a more complex and biomimetic environment.…”
Section: Methodsmentioning
confidence: 99%
“…dECM scaffolds mimic tissue‐specific components in 3D printed tissue products 65,66 . The use of decellularized scaffolds for cardiac tissue engineering application has been progressed in the past decade 22,67,68 . Ott et al in 2008, reported the first acellular rat whole heart by coronary perfusion method using a detergent solution containing 1% sodium dodecyl sulfate (SDS) and 1% Triton X‐100 in deionized water.…”
Section: Bioinksmentioning
confidence: 99%